A universal ground test equipment design for the Chang’e series spacecraft - Zhao, Wenjie; Rao, Jianing; Hao, Cheng; Jia, Wenyuan; Dong, Zhenxing; Ma, Xiaoyong; Ma, Miao; Yang, Wenhui; Zhu, Yan; An, Junshe (Frontiers in Astronomy and Space Sciences, 2025)
This paper focuses on the strategic importance of China’s Chang’e series of deep-space exploration missions and the urgent challenges faced in equipment development, and proposes a highly integrated and universal ground testing platform design. As the core component of China’s lunar exploration program, the successful implementation of the Chang’e series marks China’s technological breakthroughs and strategic layout in the field of deep-space exploration. With the completion of the world’s first lunar far-side sample return mission by Chang’e-6, subsequent missions have placed higher demands on equipment development. Traditional customized ground testing systems for single missions suffer from long development cycles and low rates of technology reuse. To address these issues, this paper proposes a universal ground testing device that integrates remote control and telemetry communication, scientific data transmission, as well as AD (Analog-to-Digital) and OC (Open Collector) signal detection, and DA (Digital-to-Analog) and Open Collector signal output functions through a modular architecture. This enables multi-mission compatibility and rapid deployment. The proposed ground testing device effectively shortens the development cycle of onboard equipment, achieves a high rate of technology reuse, and reduces costs, providing technical support for the efficient advancement of China’s deep-space exploration program.